2018
DOI: 10.1590/0100-29452018248
|View full text |Cite
|
Sign up to set email alerts
|

Perception of risk sources by chilean blueberry producers

Abstract: The biological and environmental nature of the agricultural production implies that growers operate in an environment of greater risk as compared to other economic activities. This has implications on the manner in which the growers can manage the risks inherent to their activity, which depends on how they perceive the risks and on the degree of aversion to risk. The main objective of this study was to learn about the perception of the main sources of risk that blueberry growers face in the Maule Region, Chile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The authors also found that educational attainment, age, gender, farm size, farming experience, income and location also influenced how farmers perceive the sources of agricultural risks (Duong et al, 2019). Similarly, Lobos et al (2018) found climate events to be the main source of perceived risk for blueberry producers in Chile. Aditto (2011) also found age, gender, education, off-farm work, farm size and location to significantly influence farmers' perceived risk from different sources of risk in Central and Northeast Thailand.…”
Section: Review Of Literaturementioning
confidence: 91%
See 1 more Smart Citation
“…The authors also found that educational attainment, age, gender, farm size, farming experience, income and location also influenced how farmers perceive the sources of agricultural risks (Duong et al, 2019). Similarly, Lobos et al (2018) found climate events to be the main source of perceived risk for blueberry producers in Chile. Aditto (2011) also found age, gender, education, off-farm work, farm size and location to significantly influence farmers' perceived risk from different sources of risk in Central and Northeast Thailand.…”
Section: Review Of Literaturementioning
confidence: 91%
“…, 2019). Similarly, Lobos et al. (2018) found climate events to be the main source of perceived risk for blueberry producers in Chile.…”
Section: Review Of Literaturementioning
confidence: 97%
“…The SPSS version 20.0 software was used to calculate the correlation coefficients and the various associated probabilities while the Minitab 16 was used to perform the Principal Component Analysis (PCA). This method was used in the empirical studies of Assogbadjo et al (2008), Gnanglè et al (2009), Teka andVogt (2010), andLobos et al (2018).…”
Section: Data Processing and Analysis Methodsmentioning
confidence: 99%
“…Contrarily, Miller, et al [16] argued that a variety of terminologies are used in different research for introducing various types of risks in agriculture, but production, financial, marketing, legal and human risks are considered as the most important ones. By studying the recognition of risk sources by the blueberry growers in Chile, Labos, et al [17] ranked the sources of risks as per their importance. In that ranking climatic events were identified as the most significant source of risks in blueberry cultivation perceived by the growers in Chile.…”
Section: Literature Reviewmentioning
confidence: 99%